Elderly patients discharged from an accident and emergency department–their dependency and support. Issue 4 (December 1984) - Currie, C T; Lawson, P M; Robertson, C E; Jones, A
Abstract : One hundred elderly patients who had attended an accident and emergency department and had been discharged were visited at home shortly afterwards. Compared to their previous level of function, 52 showed a minor or major increase in dependency, usually related to trauma. Scrutiny of accident and emergency records showed only scanty documentation of dependency, function and support arrangements. Available statutory services for dependent elderly in the community were under-utilized by these patients. In 39 of the 52 cases with increased dependency relatives had provided additional support.